Comparison Between Finite Element Method Simulation, Digital Image Correlation and Strain Gauges Measurements in a 3-Point Bending Flexural Test. (2015) - Ramos, Tiago; Braga, Daniel F.O.; Eslami, Shayan; Tavares, Paulo J.; Moreira, P.M.G.P.
Abstract: Mechanical testing holds a decisive role in structural components design. It supports and validates computer simulation models, spots design failures or critical sections and reveals the structure real behavior under static or dynamic loads. In order to reduce weight and/or improve durability of a train passenger car underframe, an alternative design was proposed based on an aluminium alloy modular components joined by laser beam welding. A section of this prototype was tested, according to a three-point bending flexural test configuration, and monitored with both optic techniques, such as digital image correlation and electric strain gauges. After processing, the resultant data was compared with the finite element method analysis for simulation model validation and structure inspection.